The Impact of Risk Management on the Financial Performance of Kyamuhunga Peoples Sacco: A Case Study in Bushenyi District - Abbey Nobert Linda (Uganda Christian University, 2024)
The study aimed at finding out the impact of risk management on the financial performance of Kyamuhunga Peoples SACCO, Bushenyi District. The study was guided by objectives which included; determining the influence of credit terms on the financial performance, determining the effect of credit standards on the financial performance and determining the relationship between credit policy and the financial performance of Kyamuhunga Peoples SACCO. The study was carried out using a cross sectional survey research design where both quantitative and qualitative research approaches were also used. The data were collected using questionnaires and interviews and during the data collection, both purposive and simple random sampling methods were used. A sample size of 80 employees of selected branches of Kyamuhunga Peoples SACCO (Butare branch, Bitooma branch and Ishaka branch) was also used in the study. The study findings revealed the pivotal role of effective risk management practices in shaping the SACCO’s overall financial success. The study revealed a positive consensus among respondents regarding the transparency and alignment of credit terms, the stringent adherence to credit standards contributing to portfolio quality and financial stability, and the effective communication and balance of the credit policy. The significant positive correlations identified through Pearson’s analysis further affirm the interconnectedness of these risk management components with the SACCO’s financial performance. These findings collectively emphasize the critical importance of robust risk management strategies in safeguarding and enhancing the financial health of Kyamuhunga Peoples SACCO. Finally, the study recommended the need to enhance the communication and transparency of credit terms at Kyamuhunga Peoples SACCO to further strengthen the positive perception among members. It also recommended the need for continuous reinforcement and maintenance of rigorous credit standards at Kyamuhunga Peoples SACCO and the need for sustaining and improving the effectiveness of the credit policy at Kyamuhunga Peoples SACCO. The study also recommended the need for regular monitoring and reviews of the credit policy to adapt to evolving financial landscapes and to ensure its continued relevance in achieving the SACCO's financial objectives.